A eurpean employment pact for a new european way. - Guterres, Antonio (Brussels, 1999)
Report from PES Party Leaders presented by Antonio Guterres adopted by the PES Congress on 2 March 1999
Fourth conges Milan, 1 and 2 March 1999
Engels
Brochure
Keywords: werkgelegenheid; Europa